Numerical and Experimental Multi-Approach Models for a Stone Pinnacle Reinforcement - Miquel Llorens; Miquel Àngel Chamorro; Irieix Costa; Joan Fontàs; Ester Gifra (Buildings, 2025)
The church of Saint Felix in Girona (Spain) is crowned by an octagonal bell tower with a stone pinnacle at each corner. It was built using dry-joint stone masonry, a technique that involves laying stones in a precise pattern to create a solid and durable structure. In order to strengthen the connection between the stone blocks of the pinnacles, a wooden bar was placed through a central hole carved in the stone structure. Today, the inner structure has completely disappeared. During maintenance and repair work, it was decided to restore the functionality of the disappeared reinforcement by installing a titanium bar in its place. Due to the uncertainty associated with the pinnacle’s behaviour and the lack of both, a proper numerical model of the monument, and an extensive characterization of the materials, a strategy based on multiple approaches was designed. The proposed strategy was based on combining numerical and experimental models, the final objective being to determine the length and mechanical properties of the metallic inclusion, considering the effects of gravity, wind, and seismic forces. A scale model of the pinnacle was evaluated in laboratory conditions. The results were used to calibrate a numerical model representing the scale specimen. After calibration, the results were extrapolated to a full-scale numerical model. The experimental and numerical results showed that the pinnacles needed to be reinforced along their entire height. The tensile stresses cause by wind and seismic forces at different levels, could not be compensated without the contribution of the titanium bar inserted into the pinnacle.